PENGARUH PENYULUHAN KESEHATAN REPRODUKSI TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG PERILAKU SEKS BERISIKO - Yuka OKTAFIRNANDA; Rizawati -; Mila Syari; Winda Agustina (Jurnal Maternitas Kebidanan, 2024)
Background: Adolescents are viewed as a high-risk group for sexual and reproductive health issues, because of their curiosity and wants to try something new but is not balanced with sufficient knowledge and maturity and limited experience that to encourage risky sexual behavior. Objectives: This study aimed to assess the impact of reproductive health counseling on adolescents' knowledge and attitudes regarding risky sexual behavior at SMKS M Meadan. The research employed a quasi-experimental design with a one-group pre-test-post-test approach. The population included all 280 students of SMKS “M” Medan, selected using a proportionate stratified random sampling technique. The numbers of samples in this study were 62 people. Univariate and bivariate data analyses were conducted using the Wilcoxon Pairs Test. The results indicated significant differences in respondents' knowledge levels after counseling, with a p-value of 0.02 (p < 0.05), as well as significant changes in their attitudes, also with a p-value of 0.001 (p <0 .05). The conclusion demonstrates that reproductive health counseling significantly influenced adolescents' knowledge and attitudes about risky sexual behavior at SMKS “M” Medan 2022 . It is hoped that the school can establish cross-program collaboration with the health center on reproductive health in adolescents, therefore it is expected to increase the knowledge and attitudes of adolescents about risky sexual behavior. Keywords: Counseling, Knowledge, Attitudes, Teenagers, Risky Sex